An Analysis Of Eighth Grade Students’ Writing Skill In Using Canva Application At SMPN 9 Mandau - Yola Novitasari (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2025)
Writing skill is a fundamental component of English language learning, yet many junior high school students’ experience difficulties in organizing ideas, developing arguments, and presenting coherent written texts. The integration of digital learning tools is considered an effective approach to addressing these challenges. This study aimed to analyze students’ writing skills through the use of the Canva application at SMPN 9 Mandau. The research employed a descriptive quantitative design involving 30 participants selected through cluster sampling. Participants were instructed to create narrative texts using Canva, and their writing was assessed based on seven components: main idea, argument, evidence, organization, readability, conventions, and overall impression. The findings revealed that 60% of the participants were categorized at an adequate level of writing skill, while 40% reached a high level. The results indicated that Canva contributes positively to students’ engagement, organization, and motivation in writing, although teacher guidance remains essential to strengthen critical writing aspects.